Subaltern Women Shadows of the Other in In Other Rooms Other Wonders (Journal of Gender and Social Issues, 2019)
This paper seeks to explore the status of women as subaltern and the denial of voice and agency that they suffer due to the patriarchal set up in the society as represented in In Other Rooms Other Wonders. It investigates in detail the processes involved in creation of women as subaltern in the light of Gyatri Spivak’s theory. Spivak’s definition invites us to look in detail at how the subaltern is separated from the mainstream and the mechanics involved in their discrimination. Men maintain the powerful position of the controller of resources, while women suffer as the “Other”, and are treated as “subaltern”. We can see the dynamics and machinations of this relationship within the master-slave dialect, where women are important only insofar as they serve and obey their master.
Keywords: Feminism; Subaltern; Patriarchy; voice; agency